P139 Sexual risk profiles, and sti testing behaviour among users of a postal home sampling sti testing service (PHSSTS). (8th June 2017) - Chirwa, Mimie; Ume, Uchenna; Hardie, Jamie; Nulty, Kate; Jensen, Sigrid; Doku, Eric; Hall, Angela; Pickard, Graham; Merritt, Jeremy; Day, Sara
Abstract : Introduction: The London Sexual Health Transformation Programme promises an online Postal Home sampling STI testing services (PHSSTS) for asymptomatic patients. Our aims were to pilot a PHSSTS, determine the STI prevalence, sexual risk profiles and STI testing behaviours. Methods: November 2015 – October 2016, adult patients visiting our clinic website had the opportunity to complete an online sexual health questionnaire and order a home sampling kit (HSK). Tests; Gonorrhoea, Chlamydia, Syphilis and HIV. Results were sent via SMS plus recommendations about their sexual health. Results: 946 HSK were ordered by 871 users. 650 (69%) samples were returned. Mean age 30 years; 58% female; 62% white British; 73% heterosexual: 20% MSM. 8% reused PHSSTS. 34% and 23% of users had never tested for STIs and HIV respectively. Median of 2 partners (<3 months). 43% reported condomless sex (<2 weeks) and 62% of MSM reported high risk behaviour. 29% women were not using contraception at all or correctly. 25%, 3% and 8% of all patients were eligible for Hepatitis B/C testing and Hepatitis vaccination respectively. 38% of eligible patients required Hepatitis B vaccination. STI prevalence was 3%; 1 HIV, 5 syphilis, 14 chlamydia and 1 gonorrhoea. All were recalled for treatment. Median return time for samples was 6 days. Discussion: PHSSTS proved acceptable, enhanced access and was a preferred method of testing. Additional sexual health needs could not be directly met by an online service. PHSSTS therefore must work collaboratively with GUM clinics to meet the full needs of PHSSTS users.